Effect of Applying Several Types of Foliar Fertilizers on Total N and K Levels in Leaves and Production of Apple (Malus sylvestris Mill.) Rome Beauty Varieties in Batu - Devid Khoirul Mukhtar Hadi Wijaya; Retno Suntari; Syekhfani Syekhfani (Central Research Institute For Agriculture, 2022)
The aim of this experiment is to compare the effect of foliar fertilizer application with many nutrients (AMIDA, AMIDA+, AJIFOL and BAYFOLAN) and foliar fertilizer with single nutrient (UREA) in the increasing N and K total content of leaf and apple production. The hypotheses are (1) Application of foliar fertilizer with many nutrients having better effect to N and K total content of leaf than foliar fertilizer with single nutrient, (2) Application of foliar fertilizer with many nutrients can increase apple crop product better than foliar fertilizer with single nutrient. The experiment was carried out in the orchard of apples in Batu town from July until December 2006. Soil and leaf analysis was carried out in Soil Chemical Laboratory, Faculty of Agriculture, and University of Brawijaya. Factorial trial was arranged on Randomized Complete Block Design with 3 replications. The treatment is P1=Water, P2=UREA, P3=AJIFOL, P4=AMIDA, P5=AMIDA+ and P6=BAYFOLAN. The result of experiment showed that the application of foliar fertilizer did not give significantly effect to N total content of leaf, K total content of leaf, biomass, fruit diameter, weight and amounts every tree. Application of foliar fertilizer with many nutrients having better effect to N and K total content of leaf and can increase apple crop product than foliar fertilizer with single nutrient. AMIDA+ and AJIFOL foliar fertilizer give biggest fruit diameter (7.2 cm), while the smallest fruit diameter on BAYFOLAN foliar fertilizer (6.7 cm). AJIFOL foliar fertilizer give highest fruit production equal to 59.16 ton/ha, while fruit production lowest on BAYFOLAN treatment equal to 40.42 ton/ha.